Corpus-informed instruction of the pragmatic marker I mean. Issue 4 (4th July 2022) - Caprario, Marcella; Taguchi, Naoko; Reppen, Randi
ABSTRACT: Pragmatic markers perform important communicative functions, but they can be difficult to learn in a second language because of their multifunctionality and lack of salience during communicative events. This study has two goals: (1) to describe the communicative functions of the pragmatic marker I mean in academic discourse; and (2) to provide instructional activities for teaching the multiple functions of the pragmatic marker I mean . Bottom-up corpus-linguistics techniques were used to discover frequent functions of I mean in a corpus of interactive classroom discourse. The results revealed three main communicative functions: (1) argumentation management, (2) communication management, and (3) interaction management (cf. Fant. 2016. Pragmatic markers in high-level second language use. In Advanced Proficiency and Exceptional Ability in Second Languages, ed. K. Hyltenstam, 15–42. Berlin: De Gruyter Mouton). The results also revealed a range of subfunctions, including self-correction, elaboration, rapport building, and pause filling while holding the floor. These findings provided an empirical basis for the creation of pedagogical materials. We present instructional tasks that draw on awareness-raising and explicit-inductive teaching techniques to support L2 learners in gaining a richer understanding of the multifunctionality of I mean, as well as the importance of context in interpreting and creating meaning.